Persistence of atrazine, metribuzin and simazine herbicides in two soils - Fuscaldo, Federico; Bedmar, Francisco; Monterrubbianesi, Gloria (Pesquisa Agropecuaria Brasileira, 1999)
An oat bioassay was conducted in pots under greenhouse conditions to determine the persistence of atrazine, metribuzin and simazine herbicides in soils of the southeast of Buenos Aires Province, Argentina. Atrazine rates of 0, 0.58, 1.16 and 2.32 mg g-1 of active ingredient (a.i.), metribuzin rates of 0, 0.14, 0.28 and 0.56 mg g-1 of a.i., and simazine rates of 0, 0.72, 1.45 and 2.9 mg g-1 of a.i. dry soil weight were applied to pots containing soils from Balcarce and San Cayetano sites. Organic matter (OM) content and pH of Balcarce soil were 5.5% and 5.8%, while for San Cayetano soil were 2.9% and 6.7%, respectively. Relative dry weight (RDW) of oat shoots was calculated as percentage of control. Considering a 20% RDW reduction of oat shoots, persistences of recommended rates for the region were: atrazine (1.16 mg g-1 of a.i.), 78 and 130 days after treatment (DAT) for Balcarce and San Cayetano soil, respectively; metribuzin (0.28 mg-1 of a.i.), 63 and 77 DAT for Balcarce and San Cayetano soil, respectively; simazine (1.45 mg g-1 of a.i.), 81 and 156 DAT for Balcarce and San Cayetano soil, respectively. Results show that persistence of atrazine, metribuzin and simazine in soil increased with high rates, low OM content and high pH.